The Use of HU Thresholding in Carotid-Cerebral CT Angiography: A Qualitative Study - Juliantara, I Putu Eka; Pratama, Angga (Postgraduate Program , Poltekkes Kemenkes Semarang, 2023)
Background: CT scans with contrast media administration have been used to confirm the presence of pathology in the blood vessel of the brain. High accuracy and fast scanning time produced by CT scans make this modality the main choice in assessing aneurysm pathology in the brain. Technological advances and the development of CT-helical image acquisition techniques have enabled neuroradiologists to evaluate brain aneurysms in a short time. Magnetic resonance (MR) angiography has also been reported to be useful in the diagnosis of brain aneurysms, but it is generally more time-consuming than 3D CTA, and MRI is very sensitive to movement artifacts.Methods: This research is qualitative research with an observational approach that aims to determine the management of carotid-cerebral CTA artery examination in Premier Bintaro Hospital. Unstructured interviews and documentation are used as study instruments to complete the required data.Results: Cerebral Angiography CT examination technique in Premier Bintaro Hospital uses a bolus tracking scanning technique with ROI monitoring of the Carotid Internal Artery and using triggering of 100-120 HU as a peak enhancement to ROI monitoring. This has been proven to produce optimal enhancement in the Circulus of Willis (CoW) region as Volume of Investigation (VOI) in cerebral Angiography CT-Scan. Post-processing is done by displaying images ranging from axial pre-contrast, axial post-contrast, study (pathology), MIP (Axial, coronal, sagittal), Region of Interest MIP (structure labeling), 3D VRT-bone removal.Conclusion: Scanning technique with bolus tracking and ROI monitoring of the Internal Carotid Artery and using triggering of 100-120 HU as a peak enhancement on ROI monitoring can display the arterial artery image very well so that it can be post-processed easily without reducing quality and related image information.